LEARNERS' LANGUAGE CHALLENGES IN WRITING ENGLISH - Barli Bram (Soegijapranata Catholic University, 2012)
This paper discusses a number of common linguistic challenges or issues or problems which learners (would-be teachers) of the English language encounter when attempting to express themselves in written form, particularly in paragraph writing. The paper also suggests strategies for dealing with the challenges and points out (dis)advantages of using a certain evaluation approach. Generally, the common language issues can, for example, be classified into: 1. articles, 2. concord or agreement, 3. finite verbs, 4. prepositions, 5. countable and uncountable nouns, 6. sentence levels (fragments, comma splices and run-on or fused sentences) and 7. spelling. Other general, more abstract challenges include diction or word choice, idiomatic expressions and sentence variations. The so-called Minimum Requirements, which are commonplace mistakes, as mostly listed in numbers 1-7 above and which learners (particularly those who are English teacher candidates) should avoid, are put forward and commented on. The writer believes this grammar-oriented approach still remains relevant.